Medicine Delivery Based On One Time Password (Otp) Using Drones - Srinidhi S, Vinay Kumar N, Sujay K Gowda, P R Savitha , Chappidi Lokanath Reddy (International Journal of Advanced Science and Technology, 2020)
The methodology described in this paper signifies drone as an autonomous flight controlled aerial vehicle to deliver life saving medicines with the help of telemetry signals and an android device as its vital processing unit. This Quad Copter(QC) follows the route points drawn through an android application called QGround Control and can locate and navigate to any specified destination. This paper evinces the Quad Copter’s ability to not only deliver medicines ordered online but also automatically come back to the source position using an operation called as Return To Launch(RTL). The promising outcome of this method allows future research on the use of QC to deliver any package and not just medicines.